Analisis Perilaku Konsumen dan Keputusan Pembelian Teh Tambi di Wonosobo - Amalia Nadifta Ulfa; Yohana Brenda Aprilia; Heru Irianto (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Tea is a plantation commodity that contributes to GDP and is a source of foreign exchange for the country. PT Perkebunan Tambi is a company that cultivates, processes, and markets tea. In its marketing process, PT Perkebunan Tambi has obstacles, namely the number of competitors in the market. This study aims to identify the stimulus, buyer's black box, and purchasing decisions for Tambi Tea. This identification is expected to help PT Perkebunan Tambi map several key factors consumers consider when choosing tea products. Black Box Theory consists of 3 parts: stimulation, buyer's black box, and response. This research was conducted in Wonosobo Regency from December 2023 to January 2024. The respondents in this study were 100 consumers who had bought Tambi Tea, which they obtained accidentally at markets or shops that sell Tambi Tea. The data collection technique was interviewed using questionnaires. The data is presented descriptively with data analysis using the black box theory consumer behavior model introduced by Kotler. Based on the research, consumer stimulus in the form of marketing stimulus can be explained through product, price, promotion, and distribution channels—characteristics of female consumers in the adult age group who work as housewives. The purchasing decision process includes several stages: problem recognition, information search, alternative evaluation, purchasing, and post-purchase behavior. Tambi Tea has a positive image as a local product that consumers demand from generation to generation. The cultural behavior of consuming tea in the Wonosobo community makes Tambi Tea a daily necessity. PT Perkebunan Tambi is expected to maintain quality and price so consumers are loyal.